FREQUENCY OF DEPRESSION IN DIABETIC PATIENTS VISITING TEACHING HOSPITAL (The Research of Medical Science Review, 2025)
In 2015, the International Diabetes Federation (IDF) reported that out of each 11 adults, one adult worldwide, or more than 0.415 billion people aged 20 years to 79 years, had been diagnosed with diabetes mellitus. The existence of type 2 diabetes mellitus and its associated outcomes have had a significant impact on death rates and disability rates worldwide. A complicated illness, depression is characterized by feelings of hopelessness, boredom, powerlessness, and diminished interest in once-enjoyable activities. It also involves decreased energy, a lack of zeal, dissatisfaction, and optimism. In both industrialized and developing nations, diabetes and depression are common illnesses. Research has indicated a correlation between depression and a greater risk of increasing diabetes. Likewise, there is a little increase in the likelihood of experiencing depressive symptoms if you have diabetes. Researchers in Quetta set out to determine how often depressive symptoms were experienced by diabetes patients who sought treatment at a teaching hospital. The study was conducted in the outpatient department of the medical department of Sandeman Provincial Hospital in Quetta, using cross-sectional data. There were 113 patients in this research study. Regardless of gender, every participant in the trial had to be over thirty and have been diagnosed with type II diabetes mellitus not less than five years. The study did not include participants who were receiving medication for any mental illness. Individuals with long-term illnesses such as cancer, rheumatoid arthritis, osteoporosis, chronic liver disease as well as kidney disease were not included. Insulin-dependent individuals and those who declined to participate were among the reasons for exclusion. The SPSS version 23 application was used to enter and evaluate the data. The study participants were apportioned into the following categories according to their gender: Of the total population, 53.1% were females (60 individuals), and 46.9% were males (53 individuals). The standard deviation of the 52.08-year mean age was found to be 9.30 years. The normal length of the sickness was 6.43 years, with an std dev (SD) of 2.88 years, and the duration range was 2 to 15 years. Our study's findings demonstrated that 77 patients, or 68.1%, had a nervousness diagnosis and a HADS nervousness score of more than 10. This implies that a significant number of patients suffer from anxiety. However, the HADS scale showed that 14 individuals, or 31% of the participants, showed symptoms of depression. Individuals diagnosed with diabetes who are admitted to a Quetta Teaching Hospital had a thirty-one percent chance of developing depression before leaving the hospital. We concluded that depression in diabetic patients is increasing to an alarming situation. It will affect the health of patients more than only diabetes mellitus type 2.